Pengaruh Edukasi Gizi terhadap Perubahan Perilaku Konsumsi Makanan Sehat di Wilayah Kerja Puskesmas Lubuk Pinang, Kabupaten Mukomuko Tahun 2026 - Susilawaty Susilawaty (Jurnal Multidisiplin Dehasen (MUDE), 2026)
Unhealthy dietary consumption patterns are one of the major risk factors contributing to nutritional problems and non-communicable diseases in the community. Nutrition education is a promotive and preventive strategy that can be implemented to encourage healthy eating behavior. This study aimed to analyze the role of nutrition education in changing healthy food consumption behavior among communities in the working area of Lubuk Pinang Primary Health Care. This study employed a quasi-experimental design with a pretest–posttest approach without a control group. A total of 150 community members were selected using purposive sampling. The intervention consisted of nutrition education delivered through lectures, interactive discussions, and educational media. Data were collected using questionnaires assessing nutrition knowledge, attitudes, and healthy food consumption behavior before and after the intervention. Data analysis was conducted using the Paired T-Test with a significance level of 0.05. The results showed a significant improvement in knowledge, attitudes, and healthy food consumption behavior after the nutrition education intervention (p < 0.001). It can be concluded that nutrition education plays a significant role in improving knowledge, shaping positive attitudes, and promoting healthy food consumption behavior among the community in the Lubuk Pinang Primary Health Care area.